Analysis of the Quality of Life of the Elderly in the Village of Bukit Harapan - Aszrul AB; Andi Suswani; Buharman (Comprehensive Health Care, 2018)
Quality of life is a person's perception in a cultural context and norms that are relevant to the person's place of life-related to the goals, expectations, standards, and concern for his life. The purpose of this study was to determine the quality of life of the elderly in terms of physical, psychological, level of independence, social, environmental, spiritual life in Bukit Harapan Village in 2018. This study uses a descriptive survey method with a "probability sampling" approach. The sample in this study was 78 respondents with a population of 340 determined using a sampling technique. Data collection was carried out using a questionnaire sheet (check sheet). The analysis used is a univariate analysis which is seen from the results of the frequency distribution. The study showed that the quality of life of the elderly is good as much as 75.3% and the quality of life that is less than good 25.3%. While seen from the physical domain of the good old 70.1% the physical is not good 29.9%. while the good psychology domain elderly 67.6% less good psychological 32.5%. Good independence rate of elderly 71.4% Poor independence rate 28.6%. Elderly good social domain 72.7% good social domain 27.3%. The good old neighborhood domain 67.6% and less good domain 32.5%. Spiritual good 84.4% Spiritual bad 15.7%. In this study it can be concluded that the quality of life of the elderly from the physical domain that has a less good quality is more than the good, while psychological, independence, social, environmental, spiritual elderly have a good category.